A receptor-mediated landscape of druggable and targeted nanomaterials for gliomas - Di Filippo, Leonardo Delello [UNESP]; de Carvalho, Suzana Gonçalves [UNESP]; Duarte, Jonatas Lobato [UNESP]; Luiz, Marcela Tavares [UNESP]; Paes Dutra, Jessyca Aparecida [UNESP]; de Paula, Geanne Aparecida [UNESP]; Chorilli, Marlus [UNESP]; Conde, João (Elsevier, 2023)
Gliomas are the most common type of brain cancer, and among them, glioblastoma multiforme (GBM) is the most prevalent (about 60% of cases) and the most aggressive type of primary brain tumor. The treatment of GBM is a major challenge due to the pathophysiological characteristics of the disease, such as the presence of the blood-brain barrier (BBB), which prevents and regulates the passage of substances from the bloodstream to the brain parenchyma, making many of the chemotherapeutics currently available not able to reach the brain in therapeutic concentrations, accumulating in non-target organs, and causing considerable adverse effects for the patient. In this scenario, nanocarriers emerge as tools capable of improving the brain bioavailability of chemotherapeutics, in addition to improving their biodistribution and enhancing their uptake in GBM cells. This is possible due to its nanometric size and surface modification strategies, which can actively target nanocarriers to elements overexpressed by GBM cells (such as transmembrane receptors) related to aggressive development, drug resistance, and poor prognosis. In this review, an overview of the most frequently overexpressed receptors in GBM cells and possible approaches to chemotherapeutic delivery and active targeting using nanocarriers will be presented.
Keywords: Brain cancer; Drug delivery; Glioma; Molecular machinery; Nanomedicine; Target delivery